Controls of preferential orientation of earthquake‐ and rainfall‐triggered landslides in Taiwan's orogenic mountain belt. Issue 9 (27th March 2019) - Chen, Yi‐Chin; Chang, Kang‐Tsung; Wang, Su‐Fen; Huang, Jr‐Chuan; Yu, Cheng‐Ku; Tu, Jien‐Yi; Chu, Hone‐Jay; Liu, Cheng‐Chien
Abstract: Landsliding usually occurs on specific hillslope aspect, which may reflect the control of specific geo‐environmental factors, triggering factors, or their interaction. To explore this notion, this study used island‐wide landslide inventories of the Chi‐Chi earthquake in 1999 ( M W = 7.6) and Typhoon Morakot in 2009 in Taiwan to investigate the preferential orientation of landslides and the controls of landslide triggers and geological settings. The results showed two patterns. The orientations of earthquake‐triggered landslides were toward the aspect facing away from the epicenter in areas with peak ground acceleration (PGA) ≥ 0.6 g and landslide ratio ≥ 1%, suggesting that the orientations were controlled by seismic wave propagation. Rainfall‐triggered landslides tended to occur on dip slopes, instead of the windward slopes, suggesting that geological settings were a more effective control of the mass wasting processes on hillslope scale than the rainfall condition. This study highlights the importance of the endogenic processes, namely seismic wave and geological settings, on the predesigned orientation of landslides triggered by either earthquake or rainfall, which can in turn improve our knowledge of landscape evolution and landslide prediction. © 2019 John Wiley & Sons, Ltd. Abstract : The orientations of earthquake‐triggered landslides were toward the aspect facing away from the epicenter within the areas with peak ground acceleration (PGA) ≥ 0.6 g and landslide ratio ≥ 1%, suggesting that the orientations were controlled by seismic wave propagation. Rainfall‐triggered landslides tended to occur on dip slopes, instead of the windward slopes. Endogenic processes control the orientation of earthquake‐ and rainfall‐triggered landslides in Taiwan's orogenic mountain belt.